Wajah Tafsir Sufistik di Indonesia - Wahyudi Wahyudi; Wahyudin Wahyudin (Jurnal Iman dan Spiritualitas, 2021)
This article aims to discuss the Sufistic interpretation in Indonesia. The research method used is a qualitative type through literature study. The results and discussion of this article include an overview of Sufism's history in Indonesia, the style of interpretation, and its characters. This article concludes that the Sufi interpretation emerged in Indonesia in the 17th century AD due to historical wounds in the development of Islam in Indonesia related to esoteric Islam. The emergence of Sufistic interpretation in Indonesia was motivated by Hamzah Fansuri and Syamsuddin Sumatrani. Sufistic interpretation uses the Isyari and Nadzhari interpretations with a spiritual or esoteric style.